Корейская мечта: год, который изменил жизнь - Быкова Александра (Де`Либри, 2023)
Экземпляры: ф13 (20250228) / Инвентарный номер: 67728 / Цена: 200.00 / Сис.шифр: Р2 / Авт.знак: Б 95 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6